Bioactive Components and Health Benefits of Saskatoon Berry - Lunan Zhao; Fei Huang; Amy Leung Hui; Garry X. Shen (Journal of Diabetes Research)
In response to the recent rise in numbers of diabetes patients, many treatments have been developed; but currently, oral antihyperglycemic agents and insulin are still the main clinical treatments. Since current drugs have limitations and harmful side effects, research in alternative treatments has been sought. This article reviews recent research updates of Saskatoon berries (SB), covering its background information, its main active ingredients, its structure, and its function. Flavonoid compounds in Saskatoon berries, in particular flavanol, anthocyanin, and proanthocyanin, possess anti-inflammatory, antitumor, and antidiabetes impacts. The current review synthesizes the latest research on the health benefits of Saskatoon berry in a variety of domains. With further research, SB has the potential to help treat and prevent diabetes in the future.